2013
DOI: 10.1016/j.psyneuen.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol accelerates the effects of fluoxetine on serotonin 1A receptor signaling

Abstract: A major problem with current anti-depressant therapy is that it takes on average 6–7 weeks for remission. Since desensitization of serotonin (5-HT)1A receptor signaling contributes to the anti-depressive response, acceleration of the desensitization may reduce this delay in response to antidepressants. The purpose of the present study was to test the hypothesis that estradiol accelerates fluoxetine-induced desensitization of 5-HT1A receptor signaling in the paraventricular nucleus of the hypothalamus (PVN) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…Molecular/genetic and pharmacological studies have implicated several 5-HT receptor subtypes in the behavioral effects of fluoxetine, citalopram and other 5-HT transport inhibitors. For example, the anti-depressive action produced by chronic fluoxetine administration has been attributed to changes in the level of mRNA or receptor protein, as well as to alterations in downstream signaling, associated with the 5-HT1A, 5-HT2A and 5-HT2C receptor subtypes (Brink et al 2004; Barbon et al 2011; Li et al 2012). 5-HT2B receptors also appear to be involved in the anti-depressant actions of 5-HT transport inhibitors, as the effects of fluoxetine and paroxetine were abolished in 5-HT2B receptor knockout mice compared to wild type mice in a novelty-suppressed feeding (Diaz et al 2012).…”
mentioning
confidence: 99%
“…Molecular/genetic and pharmacological studies have implicated several 5-HT receptor subtypes in the behavioral effects of fluoxetine, citalopram and other 5-HT transport inhibitors. For example, the anti-depressive action produced by chronic fluoxetine administration has been attributed to changes in the level of mRNA or receptor protein, as well as to alterations in downstream signaling, associated with the 5-HT1A, 5-HT2A and 5-HT2C receptor subtypes (Brink et al 2004; Barbon et al 2011; Li et al 2012). 5-HT2B receptors also appear to be involved in the anti-depressant actions of 5-HT transport inhibitors, as the effects of fluoxetine and paroxetine were abolished in 5-HT2B receptor knockout mice compared to wild type mice in a novelty-suppressed feeding (Diaz et al 2012).…”
mentioning
confidence: 99%
“…Interestingly, while the 90kD and 50kD bands did not completely co-localize with any marker tested in the present study, they did localize with each other and showed some overlap with the plasma membrane marker (Figure 2B). The 80kD and 35kD bands were located in the early endosome, as marked by EEA1 (Figure 2C); however, as the fractions containing the early endosome also contain cytosolic markers [18], these isoforms could be located in the cytosol as well. Finally, the 45kD and 40kD bands were predominantly located in the ER, as determined by colocalization with calreticulin (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Subcellular fractionation and isolation of the DRM from cortical tissue was performed as described previously [18]. Protein (10µg/lane) was resolved on a 12% SDS-PAGE gel followed by transfer to polyvinylidene fluoride (PVDF) membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coadministration of estradiol with luoxetine has been shown to contribute to 5-HT1A receptor desensitization [38], which is associated with antidepressant efect in humans and in rats evaluated in behavioral despair models [38]. In addition, this combination of estradiol with luoxetine inhibits 5-HTT and increases de novo brain serotonin synthesis by activating tryptophan hydroxylase enzyme [39].…”
Section: Preclinical Studies Of Serotonergic Changes Associated With mentioning
confidence: 99%